Predictive Value of the Serum Albumin Level on Admission in Patients With Spontaneous Subarachnoid Hemorrhage - Shang, Feng; Zhao, Hao; Cheng, Weitao; Qi, Meng; Wang, Ning; Qu, Xin (Frontiers in Surgery, 2021)
Objective: To determine the effect of the serum albumin level on admission in patients with spontaneous subarachnoid hemorrhage (SAH). Methods: A total of 229 patients with SAH were divided into control and hypoalbuminemia groups. The serum albumin levels were measured. The data, including age, gender, co-existing medical conditions, risk factors, Hunt-Hess (H-H) grade on admission, Glasgow coma score (GCS) on admission, complications during hospitalizations, length of hospital stay, length of intensive care unit (ICU) stay, in-hospital mortality, survival rate, outcome at discharge, and the 6-month follow-up outcome, were compared between the two groups. Results: Older age, an increased number of patients who consumed an excess of alcohol, and a lower GCS on admission were findings in the hypoalbuminemia group compared to the control group (p < 0.001). The ratio of patients with H-H grade I on admission in the hypoalbuminemia group was decreased compared to the control group (p < 0.05). Patients with hypoalbuminemia were more likely to be intubated, and have pneumonia and cerebral vasospasm than patients with a normal albumin level on admission (p < 0.001). Furthermore, the length of hospital and ICU stays were longer in the hypoalbuminemia group than the control group (p < 0.001). Hypoalbuminemia on admission significantly increased poor outcomes at discharge (p < 0.001). The number of patients with severe disability was increased and the recovery rate was decreased with respect to in-hospital outcomes in the hypoalbuminemia group than the control group (p < 0.001). Conclusion: Hypoalbuminemia was shown to be associated with a poor prognosis in patients with SAH.